The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/polym13010135
|View full text |Cite
|
Sign up to set email alerts
|

Cellulose Derived Graphene/Polyaniline Nanocomposite Anode for Energy Generation and Bioremediation of Toxic Metals via Benthic Microbial Fuel Cells

Abstract: Benthic microbial fuel cells (BMFCs) are considered to be one of the eco-friendly bioelectrochemical cell approaches nowadays. The utilization of waste materials in BMFCs is to generate energy and concurrently bioremediate the toxic metals from synthetic wastewater, which is an ideal approach. The use of novel electrode material and natural organic waste material as substrates can minimize the present challenges of the BMFCs. The present study is focused on cellulosic derived graphene-polyaniline (GO-PANI) com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(44 citation statements)
references
References 70 publications
1
33
0
Order By: Relevance
“…They suggest the observed decrease in voltage values was due to a decrease in microbial activity [24]. Yaqoob et al (2021) reported that the observed decrease in voltage generation was a consequence of a limited supply of organic substrate, which was only enough to achieve a trend of voltage generation for a 25-day period. This was followed by a decrease in the carbohydrate content for oxidation as well as bacterial activity [23].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…They suggest the observed decrease in voltage values was due to a decrease in microbial activity [24]. Yaqoob et al (2021) reported that the observed decrease in voltage generation was a consequence of a limited supply of organic substrate, which was only enough to achieve a trend of voltage generation for a 25-day period. This was followed by a decrease in the carbohydrate content for oxidation as well as bacterial activity [23].…”
Section: Resultsmentioning
confidence: 99%
“…According to Harshitha et al, (2019), the potential output depends on the growth rate of microorganisms, which depends on factors such as temperature and nutrients supplied [21]. The quick generation of potential could be explained by the swift adhesion of microorganisms to the anode electrode for biofilm formation [22] and to the oxidation of organic waste due to the bacterial community present in the MFC [23]. On the other hand, the observed decrease in voltage after the eighth day can be attributed to the combination of different events.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most crucial aspects of MFC is the substrates used due to their effect on the generation of electricity [22,23]. Various substrates can be utilized in the MFC technology to facilitate energy generation, either pure substances or complex mixture from organic materials present in wastewater.…”
Section: List Of Organic Substrates Used In Mfcmentioning
confidence: 99%
“…Among various types of conductive polymers, the most commonly used for anode electrode modification is polyaniline (PANI) [82]. It has been reported that densities of current could be improved by using PANI polymers that had been modified, such as fluorinated PANI [23] and mixture of PANI/titanium dioxide [83]. Another suitable material for anode electrode is the composite of CNTs with polyaniline [84].…”
Section: Effect Of Anode In Mfcmentioning
confidence: 99%